2014
DOI: 10.1016/j.jinf.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The burden of influenza in England by age and clinical risk group: A statistical analysis to inform vaccine policy

Abstract: Additional strategies are needed to reduce the remaining morbidity and mortality in the high-risk and elderly populations, and to protect healthy children currently not offered the benefits of vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
219
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(235 citation statements)
references
References 22 publications
13
219
2
1
Order By: Relevance
“…Previous estimates of RSV burden in secondary care in England range from 26 500 to 29 160 RSV‐associated hospital admissions per year in children <5 years of age—all lower than our estimate of 33 561 (95% CI: 30 429‐38 489) RSV‐associated admissions, which is probably due to those studies considering earlier time periods 4, 5, 6, 10. Our study found a steady, general increase in the admission rates of RSV‐associated LRTI hospital admissions from 2007/2008 to 2011/2012, peaking during the 2010/2011 season.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Previous estimates of RSV burden in secondary care in England range from 26 500 to 29 160 RSV‐associated hospital admissions per year in children <5 years of age—all lower than our estimate of 33 561 (95% CI: 30 429‐38 489) RSV‐associated admissions, which is probably due to those studies considering earlier time periods 4, 5, 6, 10. Our study found a steady, general increase in the admission rates of RSV‐associated LRTI hospital admissions from 2007/2008 to 2011/2012, peaking during the 2010/2011 season.…”
Section: Discussioncontrasting
confidence: 98%
“…Statistical models which utilise the seasonal variation in laboratory reports by pathogen can be constructed to attribute hospital admissions to different viruses 4, 5. This method of estimating the hospital burden of RSV has previously been used in the UK; however, the most recent study only considers data up to 2009 4, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 6 studied influenza seasons, we found that, while children under the age of 15 years have the highest ILI and MCIC rates, the very young (0‐4 years) and the elderly exhibit the highest rates of severe influenza‐associated hospitalizations. This is consistent with previous studies showing that young children and adolescents have the highest rates of medically attended influenza,7, 12, 13, 14 while the highest hospitalization rates for influenza are observed among very young15 and persons aged ≥65 years 16. Previous exposure to influenza viruses, providing a partial immunity to the circulating viruses, and higher vaccine coverage than in other age‐groups,17, 18 could account for the lower ILI rates at the primary care level in the elderly population.…”
Section: Discussionsupporting
confidence: 93%
“…Surveillance systems that collect ILI data may estimate iMAILI by multiplying the proportion positive for influenza among ILI patients in virological surveillance by the number of ILI patients in the population 19. We could not use this approach because syndromic surveillance collects data on MAARI, whereas virological surveillance focusses on ILI patients.…”
Section: Discussionmentioning
confidence: 99%